Progressive Muscle Relaxation to Reduce Chronic Pain in Elderly with Hypertension: A Case Study - Miftahurroziqin, Moch. Azzam; Susumaningrum, Latifa Aini; Kurdi, Fahruddin; Basri, Achmad Ali (Jurnal Kesehatan Komunitas Indonesia, 2024)
Increased blood pressure causes vascular damage to the blood vessels in the neck when carrying blood to the brain, resulting in pressure on the muscle nerve fibres, which causes head pain. One of the independent nursing interventions that can be used is Progressive Muscle Relaxation (PMR). This case study is to determine the application of PMR to reduce pain scale in elderly with hypertension at UPT PSTW Jember. This Final Scientific Work uses a descriptive design with the Case report method, which describes the application of Evidence-Based Nursing Practice, namely PMR, for headaches in the elderly with hypertension. Therapy is given to a patient in two meetings a day for seven days for 15 minutes. Measurement of pain scale using the Numeric Rating Scale (NRS). The results after being given PMR showed a decrease in pain levels by reviewing complaints of decreased pain, the average pain scale from 4.4 NRS to 3.4 NRS, the average systolic blood pressure from 155.7 mmHg to 142.8 mmHg and the average diastolic blood pressure from 94.2 mmHg to 90 mmHg. PMR therapy can reduce chronic pain by increasing the elasticity of blood vessels, reducing muscle tension and reducing headaches.